Implementasi Konsep Indoor Farming di Lingkungan Pertanian Perkotaan Kelurahan Mojolangu - Kota Malang - Hesti Triana Soelistyari; Wahyu Fikrinda; Abd Rohman; Dian Kartika Santoso; Rizki Alfian (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
The urban farming business carried out by 4 Farmer Groups in the Mojolangu Village, Malang City is an agricultural business activity with a focus on rice cultivation and vegetable horticulture. In the limited land, fertilizers and seeds as well as irrigation systems, farmers are still practicing traditional cultivation techniques with the challenges of an urban environment that has to be unproductive due to environmental pollution produced by urban activities. Based on the background of partner problems, this PKM activity specifically aims to provide additional insight to farmer groups regarding the importance of technological developments in the world of agriculture, especially for indoor farming implementation. Based on the results of the implementation of PKM activities at the Cantewa Vegetable Garden, urban agriculture activists want scheduled assistance not just only incidental from the university because the indoor farming concept is something new for partners. The presence of the Indoor Farming Concept can be a solution to the partner's problems so far, which are often constrained by pests, diseases and erratic weather. The various potentials contained in the indoor farming concept include: Being able to produce throughout the year without being limited by the season, Producing higher production and harvest frequency, Applications can be carried out in all places by requiring a relatively small area, Nutrient content in a product can reach the maximum, Healthier products and free from the use of pesticides.